The Roles of Phospholipase A2 in Phagocytes - Dabral, Deepti; van den Bogaart, Geert (Frontiers in Cell and Developmental Biology, 2021)
Phagocytic cells, such as macrophages, neutrophils, and dendritic cells, ingest particles larger than about 0.5 μM and thereby clear microbial pathogens and malignant cells from the body. These phagocytic cargoes are proteolytically degraded within the lumen of phagosomes, and peptides derived from them are presented on Major Histocompatibility Complexes (MHC) for the activation of T cells. Mammalian PLA2 isozymes belong to a large family of enzymes that cleave phospholipids at the second position of the glycerol backbone, releasing a free fatty acid and a lysolipid moiety. In human macrophages, at least 15 different PLA2 forms are expressed, and expression of many of these is dependent on pathogenic stimulation. Intriguing questions are why so many PLA2 forms are expressed in macrophages, and what the functional consequences of their altered gene expression after encountering pathogenic stimuli. In this review, we discuss the evidence of the differential roles of different forms of PLA2 in phagocytic immune cells. These roles include: lipid signaling for immune cell activation, initial phagocytic particle uptake, microbial action for the killing and degradation of ingested microbes, and the repair of membranes induced by oxygen radicals. We also discuss the roles of PLA2 in the subsequent digestion of ingested phagocytic cargoes for antigen presentation to T cells.